Label Identification And Bacteriological Quality Assessment Of Sambel Pecel (Peanuts Dressing Sauce) Product In Madiun City - Richa Dwi Fadhilah (Universitas Airlangga, 2019)
Food product requirements before distribution to consumers are including of the proper food labeling, and zero count of Eschericia coli bacteria. This study aims to identify the labeling process and bacteriological examination (Eschericia coli) on javanese peanut dressing sauce (sambel pecel) product in Madiun city. The research is an observational research whereas data is analyzeddescriptively by cross sectional study design. This study used observations andinterview in obtaining data regarding the completeness of labeling. bacteriological examination (Eschericia coli) was performed by Environmental Health Laboratory of Health Polytechnic of Ministry of Health Surabaya for the total sample of 15 sambel pecel products. All of sambel pecel products in Madiun are without a complete label andwere inconsistent with the standards of the Governmental Regulations of food label and advertisement regulation.Each product is required to implement eleven label component such as product name, composition, net weight, expiration date, name and address of producer, label of halal, and consument information for disability occurs. Five out of 15 products were positively contain Eschericia coli bacteria while the products based on regulation about food, that it must be 0 (zero). Thus it can be suggested for Trade and Industry Service of Madiun toimplement stringent selection and monitoring process before distribute the product to general population.